Palladium-Catalyzed Arylation of Benzylic C–H Bonds of Azaarylmethanes with Aryl Sulfides - Gao, Ke; Yamamoto, Keita; Nogi, Keisuke; Yorimitsu, Hideki (Synlett, 2017)
Benzylic C–H arylation of azaarylmethanes with aryl sulfides has been developed by using a Pd-NHC catalyst and an amide base. Various azaarylmethanes and aryl sulfides were involved in the reaction to afford the corresponding diarylmethanes in good to excellent yields. Moreover, triarylmethane synthesis was accomplished through iterative arylations of 2- or 4-methylpyridine with two different aryl sulfides.
Keywords: C–H arylation; palladium catalyst; aryl sulfides